2023
DOI: 10.3390/ijms24108495
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gallic Acid and Methyl Gallate Induces Apoptosis in Hela Cells through Regulation of Intrinsic and Extrinsic Protein Expression

Abstract: Induction of apoptosis is one of the targeted approaches in cancer therapies. As previously reported, natural products can induce apoptosis in in vitro cancer treatments. However, the underlying mechanisms of cancer cell death are poorly understood. The present study aimed to elucidate cell death mechanisms of gallic acid (GA) and methyl gallate (MG) from Quercus infectoria toward human cervical cancer cell lines (HeLa). The antiproliferative activity of GA and MG was characterised by an inhibitory concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Medicinal herbs are commonly used to treat various ailments, including cancer and malignancies [23,24]. Earlier studies showed that natural products could exhibit several biological activities, such as inducing apoptosis-mediated proliferation inhibition through up-regulation of bax and caspase-3 and down-regulation of bcl2 genes [25][26][27], repressing insulin-like growth factor-1 and inducing Waf-1 gene expression [28,29], glutathione S-transferase activity [30] heat shock protein [31], anti-inflammatory [32,33] and inhibitor of GLI-mediated transcription, a pathway that causes the formation and progression of a variety of tumors [34]. The natural bioactive compound of the Lamiaceae family was also reported to exert anti-proliferative activity, which inhibits oncocyte growth, induction of differentiation, apoptosis, and induces G2/M arrest on cancer cells [35][36][37], and has potential antioxidant, anti-microbe, and anti-inflammatory properties [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal herbs are commonly used to treat various ailments, including cancer and malignancies [23,24]. Earlier studies showed that natural products could exhibit several biological activities, such as inducing apoptosis-mediated proliferation inhibition through up-regulation of bax and caspase-3 and down-regulation of bcl2 genes [25][26][27], repressing insulin-like growth factor-1 and inducing Waf-1 gene expression [28,29], glutathione S-transferase activity [30] heat shock protein [31], anti-inflammatory [32,33] and inhibitor of GLI-mediated transcription, a pathway that causes the formation and progression of a variety of tumors [34]. The natural bioactive compound of the Lamiaceae family was also reported to exert anti-proliferative activity, which inhibits oncocyte growth, induction of differentiation, apoptosis, and induces G2/M arrest on cancer cells [35][36][37], and has potential antioxidant, anti-microbe, and anti-inflammatory properties [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their natural role, phenolic compounds exhibit notable pharmacological properties that encompass anti-inflammatory [44], immunosuppressive [45], cardioprotective [46], antioxidant [47], neuroprotective [48], and antimicrobial activities [49]. Moreover, several phenolic compounds have shown anticancer activity by inhibiting the growth of cancer cells [50], promoting cell death such as apoptosis [51], autophagy [52], necroptosis [53], or targeting numerous signaling pathways [54][55][56]. In addition, the formation of new blood vessels that support tumor growth has also been reported as a possible target of phenolic compounds [57][58][59].…”
Section: Phenolic Compoundsmentioning
confidence: 99%